CO2 and hydrography acquired by autonomous surface vehicles from the Atlantic Ocean to the Mediterranean Sea: data correction and validation - R. Martellucci; M. Giani; E. Mauri; L. Coppola; M. Paulsen; M. Fourrier; S. Pensieri; V. Cardin; C. Dentico; R. Bozzano; C. Cantoni; A. Lucchetta; et al. (Earth System Science Data)
The ATL2MED demonstration experiment involved two autonomous surface vehicles from Saildrone Inc. (SD) which travelled a route from the eastern tropical North Atlantic to the Adriatic Sea between October 2019 and July 2020 (see Table A6). This 9-month experiment in a transition zone between the temperate and tropical belts represents a major challenge for the SD's operations. The sensors on board were exposed to varying degrees of degradation and biofouling depending on the geographical area and season, which led to a deterioration in the measurements. As a result, some maintenance measures were required during the mission.